Remediation of Former Manufactured Gas Plants and Other Coal-Tar Sites. - Hatheway, Allen W. (CRC Press, 2011)
Over the long history of former manufactured gas plants (FMGPs) and other coal-tar-producing sites, there were an enormous variety of fuel stocks used as well as many processing and disposal methods, each leading to unique waste and site circumstances. This book supplies the historical information needed to understand and accurately predict the transport and fate of contaminants at these sites. Understanding the processes and history of a particular site is absolutely critical to performing site and waste characterization and ultimately to successful remediation. The second part of the text co.